Influenciadoras digitais nos EUA: mediações interseccionais em usos sociais de tecnologias por migrantes brasileiras - Oliveira, Luiza Dias de (2024)
This dissertation is set in the context of contemporary migratory flows, specially when it comes to the feminization of migration. Therefore, the research question sought to understand how intersectionalities mediate the uses of digital technologies by Brazilian migrant women who reside in the United States and are digital influencers. The theory of intersectionality, in this research, represents the mediation of identity from the third and fourth mediation maps, developed by Jesús Martín-Barbero. With the general objective, we seek to understand how the intersectionalities of gender, race, class, relationships, nationality and migratory status mediate the uses of digital technologies made by the interlocutors. The specific objectives of the dissertation are to analyze the relationship between the content produced by interlocutors on the digital social network Instagram and the intersectionalities experienced by them; understand how these migrant women use Instagram to self-represent themselves and share experiences about migration; identify migrants’ perception of the role of platforms in the work of digital influencers; in addition to establishing the main uses of digital technologies made by the interviewees in order to understand which intersectionalities are triggered by them. The theoretical framework chosen to support this study includes authors who address migration and transnationalism, migratory flows from Brazil to the United States, intersectional theory related to the migratory context, the feminization of migration, the uses of digital technologies by migrants, platform work and digital influencers, in addition to self-representation on digital social networks. This is a qualitative research, and an ethnography was carried out, in this case, with and in digital technologies. The observation was online, complemented with the analysis of the interlocutors' accounts on the digital social network Instagram, in addition to interviews. The observation took place between May 2022 and December 2023 on the profiles of seven migrant digital influencers. Thus, it was possible to define seven categories of analysis based on the content produced: gender, race, class, relationships, nationality, migratory status and platform work. The research shows that different intersectionalities affect not only the uses that interlocutors make of digital technologies, but also the content they produce. With multiple life contexts, each woman has a unique migratory experience, intertwined with opportunities, prejudices, the search for access to rights and working conditions. Furthermore, platform work appears to be an option for supplementing income, however, marked by informality, overload and algorithmic opacity.